The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1073/pnas.0908314107
|View full text |Cite
|
Sign up to set email alerts
|

Building biological memory by linking positive feedback loops

Abstract: A common topology found in many bistable genetic systems is two interacting positive feedback loops. Here we explore how this relatively simple topology can allow bistability over a large range of cellular conditions. On the basis of theoretical arguments, we predict that nonlinear interactions between two positive feedback loops can produce an ultrasensitive response that increases the range of cellular conditions at which bistability is observed. This prediction was experimentally tested by constructing a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 31 publications
(55 reference statements)
3
74
0
Order By: Relevance
“…Positive feedback systems have been widely used in digital electronics to engineer oscillators, switches and hysteresis where the system output can take either of two stable values, and these are each kept unless a sufficiently large input stimulus is applied [51]. A detailed discussion of positive feedback is beyond the scope of this review and can be found elsewhere [46,[52][53][54][55].…”
Section: Feed-forward and Positive Feedback Systemsmentioning
confidence: 99%
“…Positive feedback systems have been widely used in digital electronics to engineer oscillators, switches and hysteresis where the system output can take either of two stable values, and these are each kept unless a sufficiently large input stimulus is applied [51]. A detailed discussion of positive feedback is beyond the scope of this review and can be found elsewhere [46,[52][53][54][55].…”
Section: Feed-forward and Positive Feedback Systemsmentioning
confidence: 99%
“…Such a system will not respond gradually according to the intensity of a stimulus but will have an all or none response (77). Since the expression level depends upon its previous state, this kind of system is often linked to the notion of memory (77,78). It has been proposed that bistable systems are at the origin of the decision for cell differentiation (79).…”
Section: Attenuation Of Fluctuationsmentioning
confidence: 99%
“…First, the CusSR TCS responds to lower concentrations of environmental copper [3]. At standard assay condition in the laboratory, the response of modified CusSR TCS network to Cu 2?…”
Section: Discussionmentioning
confidence: 99%